Fine Mapping for Identification of Citrus Alternaria Brown Spot Candidate Resistance Genes and Development of New SNP Markers for Marker-Assisted Selection - Cuenca, Jose; Aleza, Pablo; Garcia-Lor, Andres; Ollitrault, Patrick; Navarro, Luis (Frontiers in Plant Science, 2016)
Alternaria brown spot (ABS) is a serious disease affecting susceptible citrus genotypes, which is a strong concern regarding citrus breeding programs. Resistance is conferred by a recessive locus (ABSr) previously located by our group within a 3.3 Mb genome region near the centromere in chromosome III. This work addresses fine-linkage mapping of this region for identifying candidate resistant genes and develops new molecular markers for ABS-resistance effective marker-assisted selection (MAS). Markers closely linked to ABSr locus were used for fine mapping using a 268-segregating diploid progeny derived from a heterozygous susceptible × resistant cross. Fine mapping limited the genomic region containing the ABSr resistance gene to 366kb, flanked by markers at 0.4cM and 0.7cM. This region contains nine genes related to pathogen resistance. Among them, eight are resistance homologous genes, with two of them harbouring a serine/threonine protein kinase domain. These two genes along with a gene encoding a S-adenosyl-L-methionine-dependent-methyltransferase protein, should be considered as strong candidates for ABS-resistance. Moreover, the closest SNP was genotyped in 40 citrus varieties, revealing very high association with the resistant/susceptible phenotype. This new marker is currently used in our citrus breeding program for ABS-resistant parent and cultivar selection, at diploid, triploid and tetraploid level.